2021
DOI: 10.3390/ph14070603
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Combined with Antibiotics or Antifungals against Microorganisms That Cause Skin and Soft Tissue Infections: A Planktonic and Biofilm Approach to Overcome Resistances

Abstract: The present review covers combination approaches of antimicrobial photodynamic therapy (aPDT) plus antibiotics or antifungals to attack bacteria and fungi in vitro (both planktonic and biofilm forms) focused on those microorganisms that cause infections in skin and soft tissues. The combination can prevent failure in the fight against these microorganisms: antimicrobial drugs can increase the susceptibility of microorganisms to aPDT and prevent the possibility of regrowth of those that were not inactivated dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…This is one of the disadvantages of using aPDT for infections in the clinic, the risk of microbial regrowth after its application. The combination with antimicrobials could play a crucial role to overcome this limitation of aPDT in this context [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the disadvantages of using aPDT for infections in the clinic, the risk of microbial regrowth after its application. The combination with antimicrobials could play a crucial role to overcome this limitation of aPDT in this context [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This original approach has already shown significant potential. It could help to implement the use of aPDT and reduce the amount of antimicrobials used and, thus, the multidrug resistance problem [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDT has been used in combination with several non-invasive therapeutic approaches with additive and synergistic efficacy and enhancement of outcomes in most studies conducted in vitro, as well as in preclinical and clinical applications [ 71 ]. In this regard, studies and applications have been reported for aPDT in combination with antibiotic chemotherapy [ 72 ] PTT [ 73 ], MHT [ 74 ], CAP [ 75 , 76 ], and endodontic debridement [ 77 ]. Studies and applications have also been reported in combinations using multiple PDT photosensitizers, in what could be termed multiple photosensitizer combination aPDT.…”
Section: Combination Therapies With Antimicrobial Photodynamic Therapymentioning
confidence: 99%
“…It is worthy to mention the bacterial biofilms since their tolerance against antimicrobials is much higher. Thus far, the efficacy of many PS has been already proved for the inactivation of biofilm growth although bacteria can still secrete exogenous or endogenous pigments in the biofilm that may act as ROS scavengers and reduce aPDT susceptibility [ 43 , 44 ].…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 99%
“…In general, protoberberines present the absorption bands within the UVA region and some in the UVB and visible region. Berberine (43) and palmatine (44) have two absorption bands centred at 360 and 430 nm and fluorescence at 590 and 581 nm, respectively, in organic solvents. No fluorescence or weak fluorescence was observed for protoberberines in an aqueous solution because of the aggregation or change in polarity of the local microenvironment [89,90].…”
Section: Protoberberine-like Alkaloidsmentioning
confidence: 99%